Effect of Vitamins C and E on Endothelial Function in Type 1 Diabetes Mellitus - Rachel-Marie Cazeau; Hong Huang; John A. Bauer; Robert P. Hoffman (Journal of Diabetes Research)
Background/Objectives. Endothelial dysfunction due to hyperglycemia-induced oxidative damage is an important predictor of future cardiovascular risk in patients with type 1 diabetes mellitus (T1DM) and is present in adolescent T1DM. We hypothesized that combined treatment with the antioxidant vitamins C and E might improve endothelial function (EF) and other biochemical risk factors in adolescents with T1DM. Subjects/Methods. Open-label antioxidant supplementation was given for six weeks with endpoint measurements collected at baseline and study completion. Endpoints measured included EF and plasma measurements of biochemical endothelial risk. Results. Two males and 7 females were studied. Mean age was 12.9 ± 0.9 yrs; mean T1DM duration was 5.5 ± 2.5 yrs; mean BMI was 22.1 ± 3.8 kg/m2; and mean hemoglobin A1c was 9.3 ± 1.1%. No differences were found for EF, high sensitivity CRP, total antioxidant capacity, adiponectin, or endothelial progenitor cells (EPCs) between before and after combined vitamin C and E therapy. Conclusions. Our negative study results do not support previous findings of decreased oxidative damage, improved endothelial function, and increased vascular repair capacity with antioxidant therapy. Longer term studies may be needed to determine the effects, if any, of combined antioxidant therapy on EPCs, EF, and markers of micro- and macrovascular complications in T1DM.